A novel ELISA-based crossmatch procedure to detect donor-specific anti-HLA antibodies responsible for corneal allograft rejections - Sel, Saadettin; Schlaf, Gerald; Schurat, Oliver; Altermann, Wolfgang W. (Journal of Immunological Methods, 2012)
Previous studies had shown that donor-specific anti-HLA antibodies may highly influence the survival rate of corneal allografts, although the anterior chamber generally represents an immune-privileged compartment of the eye. We postulated that the introduction of a novel crossmatch procedure for the detection of donor-specific anti-HLA antibodies in recipients awaiting a corneal graft would be adequate to investigate their influence on the outcome of the graft survival. The Antibody Monitoring System (AMS) HLA class I & II crossmatch ELISA was adapted for the use of material from the outer scleral rim instead of blood lymphocytes to isolate the donors' HLA molecules. In case of detectable donor-specific anti-HLA class I and/or class II antibodies (DSA) this result was confirmed using an identification ELISA to specify the detectable recipient's anti-HLA antibodies. PCR-based genetic tissue typing of the donors was performed also using their outer scleral rims. 45 recipients of corneal grafts were analyzed for DSA prior to or after grafting, respectively. 75% of the recipients with preformed DSA exhibited immunological complications up to the complete graft loss in four cases during the first two months. In contrast 77% of the recipients without DSA did not show any complications during the follow up period of averagely 18months. Only two cases of graft loss were observed in this group after 17 and 23months, respectively. The results demonstrate the impact of preventing donor-specific anti-HLA antibodies which are for the first time reliably detectable in any laboratory's daily work using the adapted AMS-ELISA.
EVALuna2:21105